Habituation in the Tail Withdrawal Reflex Circuit is Impaired During Aging in Aplysia californica - Kempsell, Andrew T.; Fieber, Lynne A. (Frontiers in Aging Neuroscience, 2016)
The relevance of putative contributors to age-related memory loss are poorly understood. The tail withdrawal circuit of the sea hare, a straightforward neural model, was used to investigate the aging characteristics of rudimentary learning. The simplicity of this neuronal circuit permits attribution of declines in the function of specific neurons to aging declines. Memory was impaired in advanced age animals compared to their performance at the peak of sexual maturity, with habituation training failing to attenuate the tail withdrawal response or to reduce tail motoneuron excitability, as occurred in peak maturity siblings. Baseline motoneuron excitability of aged animals was significantly lower, perhaps contributing to a smaller scope for attenuation. Conduction velocity in afferent fibers to tail sensory neurons decreased during aging. The findings suggest that age-related changes in tail sensory and motor neurons result in deterioration of a simple form of learning in Aplysia.